Composite ceramic cathode La0.9Ca0.1Fe0.9Nb0.1O3-δ/Sc0.2Zr0.8O2−δ towards efficient carbon dioxide electrolysis in zirconia-based high temperature electrolyser. (1st June 2017) - Liu, Limin; Zhou, Xiaoliang; Wang, Yong; Li, Si; Yin, Ran; Guo, Pan; Zhao, Jinggeng; Zhao, Xiaohong; Li, Bin
Abstract: In this paper, a novel composite La0.9 Ca0.1 Fe0.9 Nb0.1 O3-δ /Sc0.2 Zr0.8 O2−δ (LCFNb/ScSZ) is developed and investigated as a fuel electrode candidate for direct electrolyzing carbon dioxide (CO2 ) in solid oxide electrolysis cells (SOECs). XRD patterns of LCFNb powder sintered in CO2 at 850 °C for 10 h indicate that no secondary phases are found during the heat treatment and linear thermal expansion results prove that the LCFNb is compatible with ScSZ electrolyte used in this work. The electrolyser with porous LCFNb membrane cathode fabricated by infiltration method shows impressive electrochemical performance. The current density of 1.97 A/cm 2 at 2.0 V at 800 °C is obtained. The polarization resistance Rp of the SOEC decreases with the increase of the applied voltage between the electrodes. The obtained lowest Rp is as low as 0.113 Ω cm 2 at 2.0 V and this value is much lower than its many other perovskite and nickle-based counterparts. Besides, the LCFNb/ScSZ cathode shows excellent stability in pure CO2 at different applied voltage, especially at 2.0 V. Furthermore, the LCFNb/ScSZ electrode exhibits the current efficiencies close to theoretical ones for CO2 electrolysis, indicating that the LCFNb/ScSZ composite ceramic is an excellent cathode for zirconia-based high temperature electrolyser. Highlights: La0.9 Ca0.1 Fe0.9 Nb0.1 O3-δ is stable in both CO2 and CO at high temperatures. La0.9 Ca0.1 Fe0.9 Nb0.1 O3-δ /Sc0.2 Zr0.8 O2−δ cathode shows stable performance. The current efficiencies for CO2 electrolysis are close to theoretical ones. The lowest Rp is obtained at 2.0 V with a value of as low as 0.113 Ω cm 2 . The current density of 1.97 A/cm 2 at an voltage of 2.0 V at 800 °C is obtained.